INTEGRATION OF LMS MOODLE ENVIRONMENT INTO THE MATHEMATICAL EDUCATION - ORSZÁGHOVÁ, Dana; GREGÁŇOVÁ, Radomíra (Trends in education, 2008)
The university education is the area where information technologies and their modern means have wide usage in the form of e-learning. The teaching of mathematics is interconnected with the application of information technologies, as well. In the article we deal with the alternatives of the realization of the mathematics learning via electronics study materials. We present learning management system MOODLE and our experience of its integration into the mathematical subjects taught at the Slovak University of Agriculture in Nitra.
Keywords: teaching of mathematics; modernization of the teaching; e-learning; LMS MOODLE